Donor‐Acceptor Type Covalent Organic Frameworks. Issue 42 (15th June 2021) - Zhao, Jinwei; Ren, Junyu; Zhang, Guang; Zhao, Ziqiang; Liu, Shiyong; Zhang, Wandong; Chen, Long
Abstract: Intermolecular charge transfer (ICT) effect has been widely studied in both small molecules and linear polymers. Covalently‐bonded donor‐acceptor pairs with tunable bandgaps and photoelectric properties endow these materials with potential applications in optoelectronics, fluorescent bioimaging, and sensors, etc. However, owing to the lack of charge transfer pathway or effective separation of charge carriers, unfavorable charge recombination gives rise to inevitable energy loss. Covalent organic frameworks (COFs) can be mediated with various geometry‐ and property‐tailored building blocks, where donor (D) and acceptor (A) segments are connected by covalent bonds and can be finely arranged to form highly ordered networks (namely D−A COFs). The unique structural features of D−A COFs render the formation of segregated D−A stacks, thus provides pathways and channels for effective charge carriers transport. This review highlights the significant progress on D−A COFs over the past decade with emphasis on design principles, growing structural diversities, and promising application potentials. Abstract : Geometric structural and functional design of covalent organic frameworks (COFs) has been demonstrated as a powerful tool to construct various COFs with tailor‐made properties. Regular arrangements of donor (D) and acceptor (A) moieties in D−A COFs render the formation of segregated D−A stacks, thus provides abundant pathways and channels for effective charge carriers transport. This review highlights the significant progress on D−A COFs over the past decade with emphasis on the design principles, growing structural diversities, and promising application potentials.